Peningkatan Produktivitas Tanaman Padi Sawah Melalui Pemupukan Kompos dan NPK - I GUSTI PUTU RATNA ADI; I NYOMAN PUJA (Agrotrop : Journal on Agriculture Science, 2019)
Increased Rice Crop Productivity Through Compost and NPK Fertilization. The aims of this research was to study response of compost and NPK fertilizers to the soil chemical properties and rice yield. The method used was a factorial Randomized Block Design consisting of two factors. The first factor was compost Fertilizer (B) consists of 2 levels, namely: B0 = Without compost fertilizer and B1 = 5 ton compost fertilizer ha-1. The second factors was NPK national recomendation (P) consists of 3 levels, namely: P1 = 50% of NPK recommendation, P2 = 100% of NPK recommendation and P3 = 150% of NPK recommendation. The results showed that the treatment of compost and NPK fertilizers gave no significant effect on tillers number clumb-1 and dry straw weight/m2 , but gave a significant effect on N, P, K and dry grain weight/m2. The combination of 5 tons of compost/ha and 150% of NPK recommendation can produce N-total, P-available level, K-available and dry grain weight per m2 respectively 0.35%, 13.79 ppm, 355, 21 ppm and 0.96 kg and significantly higher than the combination of 50% NPK recommendation and without compost, which were 0.26%, 8.21 ppm, 236.10 ppm and 0.69 kg respectively.